Surgical treatment of double aortic arch in infants - Wang, Chenhan; Chen, Bingjie; Chen, Jingnan; Luo, Jinwen; Yang, Guangxian; Yi, Liwen; Deng, Xicheng (Frontiers in Pediatrics, 2025)
BackgroundDouble aortic arch (DAA) is a rare congenital vascular anomaly resulting in a complete vascular ring that encircles and compresses the trachea and esophagus, leading to respiratory and gastrointestinal symptoms. Accurate diagnosis and timely surgical intervention are essential for symptom relief and preventing complications. However, data on surgical outcomes and long-term follow-up are limited. This study retrospectively analyzed surgical outcomes and perioperative management of DAA to elucidate optimal diagnostic and therapeutic approaches.MethodA retrospective cohort study enrolled patients undergoing DAA repair (August 2015–May 2024). Participants were stratified into isolated DAA or DAA with associated intracardiac anomalies groups. Demographic, operative, and outcome variables were compared.ResultsAmong 10 patients undergoing double aortic arch repair, 6 comprised the isolated DAA group (3 males/3 females; mean age 3.70 ± 3.18 months; mean weight 6.28 ± 2.77 kg) and 4 had associated intracardiac anomalies (3 males/1 female; mean age 6.70 ± 6.12 months; mean weight 6.15 ± 3.59 kg). Isolated DAA patients and those with intracardiac anomalies showed no statistically significant differences in: symptom onset (28.17 ± 37.66d vs. 30.50 ± 41.96d), anatomic subtypes (dominant right arch 83% vs. 50%), extracardiac anomaly rates (50% vs. 75%), or clinical manifestations—respiratory (67% vs. 100%) and other systemic (17% vs. 75%) (all P > 0.05). All procedures were successfully completed with significantly shorter operative time in the isolated group (104.83 ± 22.23 vs. 233.25 ± 38.55 min, P < 0.001). No significant intergroup differences (P > 0.05) were observed in preoperative ventilation, blood loss, ventilator duration, Cardiac Intensive Care Unit stay, drainage duration, hospitalization, or complication rates. During mean 12.7-month follow-up (1–36 months), near-complete symptom resolution occurred in 9/10 survivors, with one death from respiratory failure in a comorbid patient 10 days post-discharge.ConclusionSurgical repair of double aortic arch demonstrates acceptable safety and efficacy in both infants and children, with favorable short-to-midterm clinical outcomes regardless of concomitant intracardiac anomalies.